The Librarian’s Personal Research Agenda - Babb, Maureen (Canadian Journal of Academic Librarianship / Revue canadienne de bibliothéconomie universitaire, 2025)
Personal research agendas are regular tools of scholars across academia but are infrequently discussed in the LIS literature. Instead, the literature tends to provide research agendas developed by organizations that highlight areas of research that could use more attention by LIS scholars. This perspective paper discusses how developing a personal research agenda can enhance librarians’ work as researchers and can help guide them in their research journey. It also provides insight into what a research agenda might look like and how to go about creating one.